Empowering India’s fight against cervical cancer: Harnessing routine HPV immunisation - Sudip Bhattacharya; Suneela Garg; K Madan Gopal (Journal of Family Medicine and Primary Care)
Cervical cancer, driven by human papillomavirus (HPV) infection, presents a significant health challenge in India, marked by high morbidity and mortality rates among women. This systemic review synthesises the latest research on HPV epidemiology in India, evaluates the effectiveness of existing vaccination programmes and compares India’s strategies with those of countries that have successfully mitigated cervical cancer burden. Despite available vaccines targeting high-risk HPV types, vaccine coverage remains suboptimal due to challenges, such as accessibility, vaccine hesitancy and socioeconomic barriers. Comparative analysis suggests that school-based and community engagement strategies could enhance vaccination efforts. Addressing India’s cervical cancer burden requires a multifaceted approach that includes expanding HPV vaccination coverage, implementing public awareness campaigns and adopting best practices from global successes. Economic analyses affirm the cost-effectiveness of such strategies, highlighting the potential for significant public health and financial benefits.